2021
DOI: 10.11591/ijai.v10.i4.pp830-838
|View full text |Cite
|
Sign up to set email alerts
|

Pineapple maturity classifier using image processing and fuzzy logic

Abstract: This paper describes the development of a prototype using an image processing system for extracting features and fuzzy logic for classifying the maturity of pineapple fruits depending on the colors of its scales. The standards that the system used are from Philippine National Standards for fresh fruits-pineapple for the 'queen' variant. The prototype automatically classified the maturity of queen pineapple variant grown in Munting Ilog, Silang, Cavite, Philippines. Data gathered are from the images loaded into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The indoor environment test results showed that the detection accuracy of immature and fully mature fruits was 100%, and the detection accuracy of semi-mature fruits was 86% [87]. In addition, a fuzzy logic classifier was used for classification, and the detection accuracy of semimature fruit was improved to 90% [88]. In a simulation experiment, it was found that the convolutional neural network algorithm achieved a classification accuracy of 100% for immature and fully mature pineapples, while the classification accuracy for semi-mature pineapples reached only 82% [89].…”
Section: Overripementioning
confidence: 99%
“…The indoor environment test results showed that the detection accuracy of immature and fully mature fruits was 100%, and the detection accuracy of semi-mature fruits was 86% [87]. In addition, a fuzzy logic classifier was used for classification, and the detection accuracy of semimature fruit was improved to 90% [88]. In a simulation experiment, it was found that the convolutional neural network algorithm achieved a classification accuracy of 100% for immature and fully mature pineapples, while the classification accuracy for semi-mature pineapples reached only 82% [89].…”
Section: Overripementioning
confidence: 99%
“…In Arboleda et al [18], a prototype for classifying the maturity of pineapple fruits based on the color of their scales and an image processing method for extracting features was shown. The prototype system receives the photos and segments their characteristics based on the RGB color reduction.…”
Section: Related Workmentioning
confidence: 99%
“…Edwin et al used image processing and fuzzy theory to classify post-harvest maturity into four categories. They achieved classification accuracy of 90% for partial maturity and 95% overall accuracy 10 . Note however that all of the methods described above rely on a controllable light source under indoor conditions.…”
Section: Introductionmentioning
confidence: 99%